Analysis of the Use of Technology from the Perspective of Islamic Family Law in Era 4.0 - Daharis, Ade; Rizal, Deri; Stiawan, Thoat; Iskandar, M. Yakub (Sekolah Tinggi Agama Islam Solok Nan Indah, 2023)
Industrial revolution 4.0. causing a shift in lifestyle from a social, religious pattern to a materialistic and secular individual pattern. Apart from that, the cultural sector has been disrupted due to the development of social media which has reconstructed the cultural structure of society. Social relations between communities are now more closely established in the virtual world, so that relationships in the real world have become relative. This results in a lack of direct communication with family members because they focus on seeking their own pleasure. In the era of the industrial revolution 4.0, parents have also given gadgets to their children aged around 4-6 years. This research uses a social approach method and structural functionalism as its theory. The results of the research are that families do not reject revolution and use technology to help their daily lives. Apart from that, there are implications of structural functionalism theory with the occurrence of disruption in the era of the industrial revolution, especially in the social and cultural fields of society. The Industrial Revolution Era 4.0 is an era where various things in life are filled with sophisticated technology. Several families that the author studied have used technology produced by the industrial revolution 4.0. They use it in their daily lives so that it is felt as a need and urgency. As a result, there is a shift in perspective and lifestyle in society in various areas of life, one of which is social and cultural, resulting in disruption. The disruption process has gone through a process of externalization, objectification and internalization as per the theory of structural functionalism so that both are relevant.